Specific Features of the Development of the Kazakhstani Segment of Social Networks in the Context of Bilingualism (Herald of Journalism, 2025)
The article examines the growing trends of the Kazakh-speaking audience on social networks VK and Facebook, user activity in comments, the dependence of comment language choice on the language of the post, and the prevalence of bilingualism and mixed Kazakh-Russian speech. The aim of the study is to analyze the established practice of using two languages against the background of the expanding presence of foreign social networks in Kazakhstan, the growing use of internet slang, the politicization of discourse, and, consequently, the authorities’ interest in creating national social networks. The practical and scientific significance of the work lies in identifying the global trend of the multilingual nature of social networks, studying the mutual influence of languages amid the established practice of a specific type of written-spoken communication, the tendency toward decreasing influence of distant foreign social networks, and the simultaneous attempt to promote national messengers in Kazakhstan and Russia. The research methods include statistical and content analysis, as well as comparative, inductive, and deductive approaches. The results reveal the specific features of the development of the Kazakhstani segment of social networks, which consist in transferring the bilingual conversational environment into the practice of posting and commenting, the audience’s free transition from one language to another, synthesis and borrowing, and overall mutual understanding. At the same time, a noticeable trend of increasing Kazakh-language comments has been observed in recent years, which may ultimately lead to language parity or even the predominance of the Kazakh language within Kazakhstani communities on social networks both in the near and far abroad.
Keywords: social networks, Kazakh language, bilingualism, information policy.